Hyperphosphorylated tau-based Alzheimer’s Disease drug discovery: Identification of inhibitors of tau aggregation and cytotoxicity - Hsiao-Tien Hagar; Virneliz Fernandez-Vega; Kuang-Wei Wang; Luis M. Ortiz Jordan; Justin Shumate; Louis Scampavia; April Sweet Tapayan; Hien M Nguyen; Timothy P. Spicer; Min-Hao Kuo (SLAS Discovery)
Alzheimer’s disease (AD) is a neurodegenerative disorder that affects more than 30 million people worldwide. Underlying the progressive decline of cognitive functions are the neurofibrillary tangles (NFTs) in neurons of the brain. The spatiotemporal distribution of NFTs predicts the progression of cognitive symptoms. In contrast, the senile plaques of amyloid-β aggregates, another major biomarker for AD, do not correlate with the clinical symptom development, consistent with the negligible benefits to cognitive functions in patients receiving anti-Aβ immunotherapies. A new drug discovery avenue targeting tau pathologies is therefore urgently needed. Using a recombinant hyperphosphorylated tau (p‐tau) that presents characters key to the disease, e.g., formation of neurotoxic aggregates, we conducted a fluorescence p-tau aggregation assay and completed a 100K-compound high-throughput screen (HTS) and identified inhibitors of p-tau aggregation and cytotoxicity. This dual functional screen resulted in several potent compounds that effectively curbed both p-tau aggregation and cytotoxicity. Results presented in this work are the first HTS for small-molecule compounds that target the cellular toxicity of hyperphosphorylated tau. Top hits found in this screen and their analogues to be developed in the near future may lead to breakthroughs in the therapeutic development for Alzheimer’s disease and other neurodegenerative tauopathies.